Deficiency of rds/peripherin causes photoreceptor death in mouse models of digenic and dominant retinitis pigmentosa - Kedzierski, Wojciech (The National Academy of Sciences, 2001)
Retinitis pigmentosa (RP) is a group of inherited blinding diseases caused by mutations in multiple genes including RDS. RDS encodes rds/peripherin (rds), a 36-kDa glycoprotein in the rims of rod and cone outer-segment (OS) discs. Rom1 is related to rds with similar membrane topology and the identical distribution in OS. In contrast to RDS, no mutations in ROM1 alone have been associated with retinal disease. However, an unusual digenic form of RP has been described. Affected individuals in several families were doubly heterozygous for a mutation in RDS causing a leucine 185 to proline substitution in rds (L185P) and a null mutation in ROM1. Neither mutation alone caused clinical abnormalities. Here, we generated transgenic/knockout mice that duplicate the amino acid substitutions and predicted levels of rds and rom1 in patients with RDS-mediated digenic and dominant RP. Photoreceptor degeneration in the mouse model of digenic RP was faster than in the wild-type and monogenic controls by histological, electroretinographic, and biochemical analysis. We observed a positive correlation between the rate of photoreceptor loss and the extent of OS disorganization in mice of several genotypes. Photoreceptor degeneration in RDS-mediated RP appears to be caused by a simple deficiency of rds and rom1. The critical threshold for the combined abundance of rds and rom1 is ≈60% of wild type. Below this value, the extent of OS disorganization results in clinically significant photoreceptor degeneration.